EFFECTIVENESS OF IMPLEMENTING TURMERIC AND TAMARIND HERBAL CONSUMPTION AS A COMPLEMENTARY THERAPY TO REDUCE THE PAIN SCALE OF DYSMENORRHEA IN ADOLESCENT GIRLS - Ratna Kusuma Astuti; Halima Aulia Ita Maghfiroh (JTH: Journal of Technology and Health, 2026)
Dysmenorrhea may limit the daily functioning of adolescent girls and contribute to absence from school because of lower abdominal pain arising from uterine contractions during menstruation. Turmeric and tamarind are used as herbal options for managing this condition, as their bioactive constituents may support reproductive hormone regulation and pain reduction. This study examined whether regular intake of a turmeric–tamarind preparation could reduce dysmenorrhea intensity as a complementary intervention. A quantitative pre-experimental method with a one-group pretest–posttest design was applied. Through purposive sampling, 34 female students with a history of menstruation and dysmenorrhea were recruited. Pain intensity was recorded before and after the intervention. The average score fell from 7.61 at baseline to 1.69 after treatment, producing a mean rank of 5.345. The statistical test yielded a p-value of 0.000, which was below 0.05. Thus, the turmeric–tamarind preparation was effective in lowering dysmenorrhea pain among adolescent girls. Regular use of this herbal preparation is recommended alongside a healthy diet, avoidance of spicy and oily foods and alcoholic beverages, and appropriate personal hygiene.